Effect of multimodal chemotherapy on survival of gastric cancer with liver metastasis – a population based analysis - Li, Xinghui; Chen, Zhiqiang; Zhang, Yue; Zhang, Hong; Niu, Haiyan; Zheng, Cheng; Jing, Xiaoying; Qiao, Hui; Wang, Guanhua; Yang, Wenjun (Frontiers in Oncology, 2023)
Objectives: Limited efforts have been made to evaluate the effect of multimodal chemotherapy on the survival of gastric cancer patients with liver metastases (LMGC). This study aimed to identify prognostic factors in LMGC patients and the superiority of multimodal chemotherapy with respect to overall survival (OS) in these patients. Methods: We conducted a retrospective cohort study of 1298 patients with M1 stage disease between January 2012 and December 2020. The effects of clinicopathological variables and preoperative chemotherapy (PECT), postoperative chemotherapy (POCT), and palliative chemotherapy on survival in patients with liver metastases (LM group) and non-liver metastases (non-LM group) were compared. Results: Of the 1298 patients analysed, 546 (42.06%) were in the LM group and 752 (57.94%) were in the non-LM group. The median (interquartile range) age was 60 (51-66) years. The 1-year, 3-year and 5-year overall survival (OS) rates in the LM group were 29.3%, 13.9%, and 9.2%, respectively, and those in the non-LM group were. 38.2%, 17.4%, and 10.0%, respectively (P < 0.05, > 0.05, and > 0.05, respectively.) The Cox proportional hazards model revealed that palliative chemotherapy was a significant independent prognostic factor in both the LM and non-LM groups. Age ≥55 years, N stage, and Lauren classification were also independent predictors of OS in the LM group (P < 0.05). Palliative chemotherapy and POCT were associated with improved OS compared with PECT in the LM group (26.3% vs. 36.4% vs. 25.0%, P < 0.001). Conclusion: LMGC patients had a worse prognosis than non- LMGC. Number of metastatic sites more than 1, liver and other metastatic sites, no CT treatment and HER2-negative had a poor prognosis. LMGC patient may benefit more from palliative chemotherapy and POCT than from PECT. Further well-designed, prospective studies are needed to validate these findings.